Implementasi Sistem Basis Data pada Sektor Pendidikan di Indonesia - Annisa Rahmawita; Tania Azura Fahani; Rohima, Rohima; Alwi Alviansha; Nurbaiti, Nurbaiti (Yayasan Literasi Sains Indonesia, 2023)
DBMS (Database Management System) is a software system that enables database users to maintain, control and access data in a practical and efficient manner. This DBMS is the layer that connects the database with application programs to ensure that the database remains consistently organized and can be accessed easily. The main purpose of using a DBMS in the education sector is to avoid confusion in terms of processing large amounts of data and to help students process data. DBMS also reduces and eliminates data redundancy and maximizes data consistency so that every time it displays data, the data is in accordance with the original. The main function of the DBMS is data storage, due to the complexity of the current DBMS, various types of data can be stored. The results of this study are that database management systems are urgently needed in the education sector so that they can progress and be able to compete, can help process student data, and can be used to create school profiles.